Filosofi Pola Pekarangan dan Rumah Tradisional, Obyek Studi di Desa Bayung Gede - Bangli - A A Gde Djaja Bharuna S.; I Ketut Muliawan Salain; Anak Agung Ngurah Aritama (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2023)
Kintamani has several Bali Aga villages. Bayung Gede is one of them, which is an old settlement that has distinct cultural and architectural features. It is geographically positioned on a mountainous terrain of 800-900 metres above sea level. Its chilling climate condition impacts the spatial formation of its traditional homes, including layout patterns, building functions, opening patterns, and building forms. A combination of all of these attributes creates Bayung Gede as a settlement with a unique physical formation. Space within a house compound directly adjacent to the rurung (community road) is categorised as a sacred zone. This article aims to identify the philosophical elements of settlement and homes of the Bayung Gede community. It describes building forms, spatial patterns, and various uniqueness of Bayung Gede’s traditional houses. Furthermore, it breaks down design elements, which include home patterns, orientation, zoning, circulation and building layouts that are restricted to those meant for living only. Within, it addresses the study of form, scale, and proportion. Data is gathered through observations, architectural documentation, and interviews. For the aforementioned study, a descriptive-naturalistic research approach is used. It is concluded that the design of traditional homes in Bayung Gede Village is well-founded by a particular philosophy that makes this settlement unique compared to other Bali mountainous villages in Bali.Keywords: philosophy; housing compound; house layout; building form AbstrakKitamani memiliki beberapa desa Bali Aga. Bayung Gede adalah salah satunya yang merupakan desa kuno dengan ciri khas dalam budaya dan arsitekturnya. Topografi daerah pegunungan (800-900 M, dpl) berhawa sejuk berpengaruh terhadap pola penempatan, fungsi ruang, pola bukaan ruang, serta bentuk bangunan. Keunikan pada penataan bangunan rumah yakni hierarki nilai yang berlawanan di kanan dan kiri jalan lingkungan. Pada setiap rumah, zona yang paling dekat dengan sumbu jalan (rurung), merupakan zona sakral. Tujuan penulisan adalah untuk menemukenali filosofi yang terkandung pada rumah tradisional dengan mendeskripsikan bentuk bangunan, pola, serta keunikan-keunikan rumah tradisionalnya. Selanjutnya mengurai unsur-unsur perancangan yakni: pola rumah, orientasi, zoning, dan sirkulasi; dan tata bangunan yang dibatasi hanya pada fungsi hunian. Kemudian kajian bentuk, skala, dan proporsi juga ditujukan di dalamnya. Pendataan dilakukan melalui observasi, dokumentasi, dan wawancara. Metode penelitian dengan karakteristik seperti ini, mempergunakan deskriptif-naturalistik. Dapat disimpulkan bahwa terdapat filosofi yang melatarbelakangi pola pekarangan dan rumah tradisional di Desa Bayung Gede yang membuat permukiman ini unik jika dibandingkan dengan desa-desa pegunungan lainnya yang ada di Bali.Kata kunci: filosofi; pekarangan rumah; layout rumah; tata bangunan